January Effect Analysis on The Indonesian Stock Market (Case Study of the 2016-2020 LQ45 Index Stock) - Risma Dewi; Farida Ratna Dewi (Universitas Binaniaga Indonesia, 2022)
The January effect anomaly that occurred in the Indonesian stock market was inconsistent and only occurred in a few years. However, its existence is sufficient to create a potential negative return risk in the non-January trading month. So this research purposes to identify the characteristics of the January effect anomaly that occurs and its effect on abnormal stock returns in the long term of five years. The research sample contains 27 publicly listed company stocks in the LQ45 index from 2016 to 2020. The analytical tool used in this research is a multiple linear regression model with panel data method. This research finds that the January effect anomaly only occurs in some stocks in the LQ45 index. The peak occurred in 2018 and 2019. According to the regression test, it was found that the January effect anomaly had no significant effect on stock abnormal returns. Thus, the recommendation for investors is not to overreact to the January effect anomaly. As well as maintaining the efficient condition of the Indonesian stock market by conducting fair share trading.